Human Resource Planning at Special Growth and Development Hospital: Realizing Optimal Service - Iin Inayah; Rhian Indradewa; Tantri Yanuar Rahmat Syah; Rian Adi Pamungkas (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Human Resource (HR) planning in healthcare service management at the Growth and Development Special Hospital in Region X focuses on workforce development to meet future service needs. This study analyzes the implementation of BPJS-based healthcare services for child growth and development, and evaluates its long-term sustainability. This study uses a qualitative method with a descriptive approach through literature studies, observations, interviews, surveys, and documentation. The analysis focuses on internal and external factors that influence the success of healthcare services. The Growth and Development Special Hospital implements a strategy based on the McKinsey 7S model to ensure alignment of values, organizational culture, and HR management practices with the hospital's vision and mission. The servant leadership approach is applied to create a positive work environment that encourages innovation and collaboration. Through a transparent recruitment system, needs-based competency development, and ongoing training, this hospital seeks to improve the competitiveness and quality of healthcare services for pediatric patients with growth and development disorders, while supporting government programs in reducing stunting rates and realizing Indonesia's golden generation.